Impact of the extinct megaherbivore Steller's sea cow (Hydrodamalis gigas) on kelp forest resilience - Roopnarine, Peter D.; Banker, Roxanne M. W.; Sampson, Scott D. (Frontiers in Ecology and Evolution, 2022)
Giant kelp forests off the west coast of North America are maintained primarily by sea otter (Enhydra lutris) and sunflower sea star (Pycnopodia helianthoides) predation of sea urchins. Human hunting of sea otters in historic times, together with a marine heat wave and sea star wasting disease epidemic in the past decade, have devastated these predators, leading to widespread occurrences of urchin barrens. Since the late Neogene, species of the megaherbivorous sirenian Hydrodamalis ranged throughout North Pacific giant kelp forests. The last species, H. gigas, was driven to extinction by human hunting in the mid-18th century. H. gigas was an obligate kelp canopy browser, and its body size implies that it would have had a significant impact on the system. Here we hypothesize that sea cow browsing would have promoted a denser understory algal assemblage than is typical today, thereby providing an alternative food resource for urchins, resulting in enhanced forest resilience. We tested this hypothesis with a mathematical model, comparing historical and modern community responses to marine heat waves, sea star wasting disease, and the presence of sea otters. We found that forest communities were highly resistant to marine heat waves, yet susceptible to sea star wasting disease, and to disease in combination with warming. Resistance was greatest among systems with both sea cows and sea otters present. Most simulations that transitioned to barrens did so temporarily, recovering after about 10 years. Historical communities, however, exhibited delayed transitions after perturbation relative to modern communities and faster recovery times. Sea cow browsing facilitated denser algal understories, enhancing resilience against modern perturbations. We propose that operationalizing these findings by mimicking the ecological impact of sea cow herbivory could enhance kelp forest resilience.